2016
DOI: 10.2147/cia.s101902
|View full text |Cite
|
Sign up to set email alerts
|

Managing infective endocarditis in the elderly: new issues for an old disease

Abstract: The incidence of infective endocarditis (IE) rises in industrialized countries. Older people are more affected by this severe disease, notably because of the increasing number of invasive procedures and intracardiac devices implanted in these patients. Peculiar clinical and echocardiographic features, microorganisms involved, and prognosis of IE in elderly have been underlined in several studies. Additionally, elderly population appears quite heterogeneous, from healthy people without past medical history to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 67 publications
5
58
0
5
Order By: Relevance
“…Infective endocarditis (IE) is a life-threatening disease with high morbidity and mortality [1][2][3][4]. Its incidence in older patients has increased for different reasons, such as the aging of the general population and the increasing percentage of comorbidities [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infective endocarditis (IE) is a life-threatening disease with high morbidity and mortality [1][2][3][4]. Its incidence in older patients has increased for different reasons, such as the aging of the general population and the increasing percentage of comorbidities [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Its incidence in older patients has increased for different reasons, such as the aging of the general population and the increasing percentage of comorbidities [5][6][7][8][9][10][11][12][13][14]. Clinical presentation seems to be similar between the younger and older population [15][16][17][18][19]; however, there is no agreement on the role of age in general mortality or in the mortality related to surgery as a treatment for IE [2,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found the in-hospital mortality rate and one-year mortality rate in older patients was much higher than the younger patients, which was consistent with previous reports. [3,14,15,18,19] As reported previously, older adults were prone to require complex care needs and suffer from multiple comorbidities, which made them vulnerable to health-associated exposure and poor outcomes. [14,[20][21][22]Besides, the lower operative rate in older patients compared with the younger in our cohort may be another important reason for the higher mortality in older patients.…”
Section: The Clinical Characteristics Of Older Patients With Infectivmentioning
confidence: 98%
“…This phenomenon was frequently presented in previous reports. [3,26,27] The main consideration may be the increasing risks during the perioperative period owing to the decline in organ function and the presence of comorbidities associated with aging. These factors made the choice of surgical treatment for elderly patients more difficult.…”
Section: Surgical Therapy and Prognosis For Patients≥65 Year Old Withmentioning
confidence: 99%
“…Modifications of fat mass alter the volume of distribution of antibiotic according to their lipophilia. Decreased albumin level reduces transport of highly protein-bound drugs (such as vancomycin) and the resulting drug-free fraction 7. Decreased renal function reduces the renal drug clearance.…”
mentioning
confidence: 99%